Global Challenges in Responsible Business - Smith, N. Craig; Bhattacharya, C. B.; Vogel, David; Levine, David I. (Cambridge : Cambridge University Press, 2010)
Corporate responsibility has gone global. It has secured the attention of business leaders, governments and NGOs to an unprecedented extent. Increasingly, it is argued that business must play a constructive role in addressing massive global challenges. Business is not responsible for causing most of the problems associated with, for example, extreme poverty and hunger, child mortality and HIV/AIDS. However, it is often claimed that business has a responsibility to help ameliorate many of these problems and, indeed, it may be the only institution capable of effectively addressing some of them. Global Challenges in Responsible Business addresses the implications for business of corporate responsibility in the context of globalization and the social and environmental problems we face today. Featuring research from Europe, North America, Asia and Africa, it focuses on three major themes: embedding corporate responsibility, corporate responsibility and marketing, and corporate responsibility in developing countries.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Social responsibility of business; Corporate culture